Pengaruh Lingkungan Inerja Karyawan dan Motivasi terhadap Kinerja Karyawan Pada PT BFI Finance Tbk - Widowati, Widowati; Juanda, Angga; Wati, Lia (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The importance of this research stems from the need to understand how these two factors influence employee performance, which is critical for organizational success. This study aims to examine the impact of the work environment and motivation on employee performance at PT. BFI Finance Indonesia Tbk, both individually and collectively. The research employs a quantitative descriptive method with a total population of 82 employees, using a saturated sampling technique, where all 82 individuals were selected as respondents. Data analysis includes regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The findings reveal that the work environment has a significant positive impact on employee performance, indicating a strong correlation between these two variables. The research further shows that motivation also significantly influences employee performance, with a similar strong relationship observed between motivation and performance. When both variables are considered together, the results suggest that both the work environment and motivation contribute significantly to employee performance. These findings imply that enhancing the work environment and fostering motivation could lead to improved employee performance. The study's implications emphasize the importance of creating a supportive and motivating work environment as a strategy for improving employee productivity and organizational effectiveness.